Game Theory Analysis of Options - Marek, Petr (2020)
This diploma thesis aims to derive the critical value of bank’s equity, which triggers depositors to withdraw their deposits and by doing so trigger a bank run. Thesis is divided into theoretic and application part. In the theoretic part, the basics of option pricing and game theory are introduced. Afterwards, both disciplines are combined and the theoretical model of a bank run is presented. In the application section, these theoretical discoveries are used to calculate three possible equity values, which lead to the unique scenarios of depositors ́ behavior. This bank run is examined on popular Czech bank named Air Bank a. s. Within the scope of the most likely scenario is eventually conducted liquidity stress test, which simulates a potential run on Air Bank a. s.